GFP-Based Fluorescence Assay for CAG Repeat Instability in Cultured Human Cells - Santillan, Beatriz A. (PLoS One, 2014)
Trinucleotide repeats can be highly unstable, mutating far more frequently than point mutations. Repeats typically mutate by addition or loss of units of the repeat. CAG repeat expansions in humans trigger neurological diseases that include myotonic dystrophy, Huntington disease, and several spinocerebellar ataxias. In human cells, diverse mechanisms promote CAG repeat instability, and in mice, the mechanisms of instability are varied and tissue-dependent. Dissection of mechanistic complexity and discovery of potential therapeutics necessitates quantitative and scalable screens for repeat mutation. We describe a GFP-based assay for screening modifiers of CAG repeat instability in human cells. The assay exploits an engineered intronic CAG repeat tract that interferes with expression of an inducible GFP minigene. Like the phenotypes of many trinucleotide repeat disorders, we find that GFP function is impaired by repeat expansion, in a length-dependent manner. The intensity of fluorescence varies inversely with repeat length, allowing estimates of repeat tract changes in live cells. We validate the assay using transcription through the repeat and engineered CAG-specific nucleases, which have previously been reported to induce CAG repeat instability. The assay is relatively fast and should be adaptable to large-scale screens of chemical and shRNA libraries.